2020
DOI: 10.1038/s41598-020-73450-0
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactive sensorimotor cortex during voice perception in spasmodic dysphonia

Abstract: Spasmodic dysphonia (SD) is characterized by an involuntary laryngeal muscle spasm during vocalization. Previous studies measured brain activation during voice production and suggested that SD arises from abnormal sensorimotor integration involving the sensorimotor cortex. However, it remains unclear whether this abnormal sensorimotor activation merely reflects neural activation produced by abnormal vocalization. To identify the specific neural correlates of SD, we used a sound discrimination task without over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Although the pathophysiology of LD is not fully known, it has been suggested that LD is a functional and structural disorder involving a complex neuronal network comprising basal ganglia structures, the thalamus, and their connections with cortical areas, the cerebellum, and sensorimotor cortex [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Alterations in activity of speech-related areas mediating motor preparation and execution were reported in the primary motor cortex for oro-laryngeal muscle representation, the middle frontal gyrus, the inferior frontal gyrus (i.e., Broca’s area) [ 48 , 50 , 53 , 54 , 55 , 56 , 57 ], and the temporal [ 48 ] and parietal brain areas [ 58 ].…”
Section: Patho- Neurophysiology Of Ldmentioning
confidence: 99%
“…Although the pathophysiology of LD is not fully known, it has been suggested that LD is a functional and structural disorder involving a complex neuronal network comprising basal ganglia structures, the thalamus, and their connections with cortical areas, the cerebellum, and sensorimotor cortex [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Alterations in activity of speech-related areas mediating motor preparation and execution were reported in the primary motor cortex for oro-laryngeal muscle representation, the middle frontal gyrus, the inferior frontal gyrus (i.e., Broca’s area) [ 48 , 50 , 53 , 54 , 55 , 56 , 57 ], and the temporal [ 48 ] and parietal brain areas [ 58 ].…”
Section: Patho- Neurophysiology Of Ldmentioning
confidence: 99%